'BioDun J. Ogundayo and Julius O. Adekunle (eds.), African Sacred Spaces: Culture, History, and Change. (16th February 2022) - Sheridan, Michael
Abstract : 'BioDun J. Ogundayo and Julius O. Adekunle (eds.), African Sacred Spaces: Culture, History, and Change (Lanham, MD: Lexington Books, 2019), 268pp., $100 (hbk), ISBN: 9781498567428.